The Quaker Renaissance and Liberal Quakerism in Britain, 1895-1930: Seeking a Real Religion - Dales, Joanna (Brill Research Perspectives, 2020)
Front Matter -- Copyright page -- The Quaker Renaissance and Liberal Quakerism in Britain, 1895-1930.